Sistemska in nomotehnična vprašanja splošnih pravnih aktov javnega zavoda - Igličar, Albin (Pravni letopis, 2016)
Adoption of general legal acts is going on in an organized way also in some self-managing communities and public institutions. Already by tradition such a function belongs to local self-government and to religious organizations and scientific corporations (statutes of towns and/or municipalities, general acts of canon law, statutes of universities), and in modern society to various companies and syndicate associations (statutes of joint-stock companies, collective agreements) and public institutions. In this way pluralism of the legal system is being enforced and monopoly of the state in setting general legal norms is diminishing. Organs of self-managing organizations and communities supplement the role of legal institutions.
Keywords: javni zavodi; nomotehnika; osnovne šole; pravni akti; zakonodaja